ISLAMIC PERSPECTIVE ON BUSINESS ETHICS - Ernawati, Siswanta & (PROCEEDING INTERNASIONAL SEMINAR, 2015)
The purpose of this paper is to present a corelation among business player included person, organisation dan goverment as a stakeholeder of Islamic business ethic. It explores the normative and practical of business ethics in the context of Islamic religious perspective to organization and personal business man. It briefly this paper discribed the foundations of Islamic business ethic and use holly Qurâan and Al Hadis as a primary references.Keywords : Business ethic, Islamic, relation.